PENGGUNAAN METODE RALLY TABLE UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA KELAS SATU DALAM MENULIS TEKS DESKRIPTIF DI SMAN 5 PEKANBARU - Prasedya, Yayang; Ras, Fakhri; ', Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research activity is to find out the contribution of rally table method to improve the writing skill of the first year students of SMAN 5 Pekanbaru. The participants were 39 students. The data was collected by using observations, tests, and field notes. The data was analyzed by quantitative and qualitative. The research finding showed that the implementation of rally table method as the teaching method could improve students’ writing ability both at the first cycle and second cycle. The finding also proved that in the pre-test students’ average score was only 44 and it improved to 56 in the post-test 1, and finally improved to 76 in the post-test 2. It was also proved that applying the procedures of rally table method in teaching writing could raise students’ interest and motivation to learn and share ideas with their groups since the core of rally table method was a collaboration between groups or pairs. In addition, applying rally table as a teaching method in English language teaching and learning could also improve students’ ability to writing in English in terms of grammar, vocabulary, mechanic, fluency, and organization. Since Rally Table method has been proven effective in teaching writing a descriptive text, it was suggested that English teachers apply this method in order to improve students’ writing skill.Keywords: Rally Table, Students’ Writing Ability and Descriptive Text